2006
DOI: 10.1111/j.1523-1739.2006.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Approach to Evaluation of Umbrella Species as Conservation Surrogates

Abstract: Although species with large area requirements are sometimes used as umbrella species, their general utility as conservation tools is uncertain. We surveyed the species diversity of birds, butterflies, carabids, and forest-floor plants in forest sites across an area (1,600 km2) in which we delineated large breeding home ranges of Northern Goshawk (Accipiter gentilis). We tested whether protection of the home ranges could serve as an effective umbrella to protect sympatric species of the four taxa. We also used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 57 publications
(63 reference statements)
1
83
2
2
Order By: Relevance
“…In contrast, the relatively high occurrence for generalist owls across all sites makes them less reliable surrogates. This result for the generalist owl is similar with patterns suggested by Ozaki et al (2006) for Accipiter gentilis, who found that this raptor was not an efficient biodiversity surrogate because it often used anthropogenically degraded habitat that were poor in taxonomic diversity. The latter study, however, did not account for the detectability of both the surrogate candidate and target biodiversity, and it did not test for other dimensions of target biodiversity such as endemism or functional diversity.…”
Section: Evidence For a Reliable Surrogacy Relationshipsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, the relatively high occurrence for generalist owls across all sites makes them less reliable surrogates. This result for the generalist owl is similar with patterns suggested by Ozaki et al (2006) for Accipiter gentilis, who found that this raptor was not an efficient biodiversity surrogate because it often used anthropogenically degraded habitat that were poor in taxonomic diversity. The latter study, however, did not account for the detectability of both the surrogate candidate and target biodiversity, and it did not test for other dimensions of target biodiversity such as endemism or functional diversity.…”
Section: Evidence For a Reliable Surrogacy Relationshipsupporting
confidence: 77%
“…Therefore, stand-level structural complexity may be the driver of a positive association between the surrogate candidate and target biodiversity (Drever et al 2008, Lindenmayer et al 2014a). Furthermore, it can expected that not all members of the top predator guild will be reliable surrogates because those that are habitatgeneralists may be able to adapt to degraded habitats (Ozaki et al 2006, RodrĂ­guez-Estrella et al 2008. Studies identifying the potentially contrasting role of specialist and generalist predators as surrogates for functional diversity and endemism will contribute significantly to applied ecology (Martin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Roberge and Angelstam (2004) proposed that the idea of umbrella species could be used to assess minimum size but also to help in selecting the locations of potential reserves and to determine the composition, structure and processes of ecosystems. Other authors think in a simpler way that umbrella species are large and often wide-ranging animals whose requirements encompass those of many other species (Groom et al 2006) and whose protection, even if they are invertebrates, offers protection to other species sharing the same habitat (Ozaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several species assemblages have been selected as surrogates based on characteristics that include, among others, their functional role, distribution, threat status or charismatic value (e.g., Bonn et al, 2002Bonn et al, , 2004Ozaki et al, 2006). Still, taxonomic groups are the most commonly applied surrogates.…”
Section: Introductionmentioning
confidence: 99%